(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Intraoperative awareness (IOA) is a rare but psychologically distressing complication where patients recall events under general anesthesia. Although global incidence ranges between 0.1–0.2percent, recent regional studies suggest higher rates due to limited monitoring resources. Intraoperative dreaming is more common, though often benign, but may indicate light anesthesia. There is limited data on IOA and dreaming incidence in Pakistan’s elective surgery population. Objectives: This study aimed to determine the incidence of intraoperative awareness and dreaming among patients undergoing elective general surgeries under general anesthesia in tertiary hospitals of Peshawar. Methods: A cross-sectional observational study was conducted on 311 adult patients undergoing elective general surgeries under general anesthesia. Data was collected within 24 hours postoperatively using the Modified Brice Questionnaire. Statistical analysis included descriptive frequencies for associations using SPSS version 27. Results: Overall, 3.5% of patients reported intraoperative awareness, with the most common recall being feeling pain (18.2%) and hearing voices (18.2%). Additionally, 6.4% reported dreaming during anesthesia, and among those, 1.6% described their dreams as disturbing. Pain (34.1%) and anxiety (24.1%) were the most frequently reported worst perioperative experiences. Conclusions: The incidence of intraoperative awareness (3.5%) and dreaming (6.4%) in this study is higher than global estimates, underscoring the need for improved depth monitoring and structured postoperative assessments to identify and manage such experiences, ensuring safer and more patient-centered anesthesia care.